Impact of TCSC Installation on ATC in a System Incorporating Wind and Hydro Generations. (2016) - Gupta, Abhishek; Kumar, Ashwani
Abstract: This paper examines the impact of installing Thyristor Controlled Series Compensator (TCSC) on Available Transfer Capability (ATC) in a system with wind and hydro generations. Wind resource is modelled as an active power generation, wind power being decided by average wind velocity values over 24 hour duration. Hydro power output is represented as a polynomial in two variables, water discharge and volume of water in the reservoir. The variation in ATC is first observed with varying wind and hydro generations over 24 hours and then a steady state model for TCSC is used to bring out its effect on ATC. The ATC values with TCSC are obtained by varying the location of the device through different lines. The site which gives the maximum values for ATC is chosen as the optimal placement of TCSC. Modified IEEE 24 bus reliability test system (RTS) is used for the study.